Analysis of Light Fidelity (LiFi) Network Implementation - Idwan Harry; Syarifuddin Syarifuddin (Institute of Computer Science (IOCS), 2021)
The existence of Wifi which is the main facility in life demands an increase in internet network performance in the future. Technology continues to develop, innovating the creation of internet network access methods such as Light Fidelity (LiFi). The current internet network access speed has reached 10 Gbps (called 5G) using WiFi, while the LiFi generation access speed reaches 100 Gbps, where LiFi is classified as Internet of Things (IoT) technology. LiFi data is transmitted by an LED bulb and received by a sensor that converts light into electrical waves (photoreceptors) [1]. The working principle of LiFi technology is (1) the LED can be turned on and off very quickly which provides a good opportunity for data transfer in the form of a Binary code (a series of numbers 0 and 1 or also called off and on); (2) Turning on the LED is logic '1' is called on, switching LED is logic '0' is called off. (3) It is possible to encode the data into the LED using a controller so that the LED blink can be varied when the data to be encoded on the 0 and 1 strings is different. (4) using a micro-LED light bulb the data transmission speed reaches 10 Gbps using LiFi [2]. The specific purpose of this research is to inform the public about the advantages and disadvantages of LiFi technology. The research stages consist of (1) Analysis of the LiFi access speed of transferring data that reaches 100 Gbps compared to WiFi which only reaches 7 Gbps (which has been carried out by Oxford University and University College). (2) Analyze and evaluate the performance of LiFi so that the network implementation will be able to control the obstacles that always occur in bandwidth (especially throughput) such as WiFi networks. Research methods include research subjects focused on previous research [1] so that recommendations for the development of LiFi network infrastructure are achieved, namely optimization of throughput as an indicator and evaluation of the real condition of bandwidth (quality of successfully transferred data). Based on this, the object or target that becomes the determinant is to control and overcome obstacles in the LiFi network transferring data packets. The results showed that the waves or light beams used as communication lines in LiFi technology were able to carry more data and information than radio waves in WiFi technology. This is evidenced by the bandwidth using LiFi is doubled compared to WiFi. LiFi is capable of transmitting data at speeds up to 224 Gbps (GB/second-gigabyte/second), while WiFi is between 300-720 Mbps (MB/second-megabyte/second). Then LiFi uses ordinary LED lights, not using special LED lights. The contribution of the research results is expected to increase throughput through control strategies and reduce weaknesses that arise during the data transfer process.